Facile synthesis of a triptycene‐based porous organic polymer with a high efficiency and recyclable adsorption for organic dyes. Issue 39 (29th May 2019) - Li, Yajing; Wang, Haijiang; Zhao, Weifeng; Wang, Xiaoqin; Shi, Yidong; Fan, Haojun; Sun, Hui; Tan, Lin
ABSTRACT: Water contamination resulting from organic dyes has had severe detrimental effects on human health and environmental tolerance. To address this issue, a delicate strategy for taking host–guest function in porous organic polymers via a facile Friedel–Crafts reaction of triptycene and post‐modification was achieved. By means of this route, a sulfonic acid functionalized triptycene‐based porous organic polymer (TPOP–SO3 H) with a hierarchical structure and a desirable Brunauer–Emmett–Teller value of 1002 m 2 /g was synthesized this study. The TPOP–SO3 H material demonstrated a maximum adsorption capacity for methylene blue of 97.1 mg/g. Remarkably, an absorption efficiency of more than 90% of TPOP–SO3 H was observed even after five cycles. Therefore, such a hierarchical porous organic polymer can be highly recommended as one type of promising material for the treatment of organic dye‐polluted wastewater. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47987. Abstract :